Kegiatan Skrining Kesehatan Kulit Wajah dan Penuaan Kulit pada Populasi Dewasa di Sekolah SMP Kalam Kudus - Ruslim, Welly Hartono; Firmansyah, Yohanes; Gunaidi, Farell Christian; Satyanegara, William Gilbert; Teguh, Stanislas Kotska Marvel Mayello; Santoso, Alexander Halim (STIKes Ibnu Sina Ajibarang, 2024)
Aging causes significant physiological changes in the skin, mainly due to decreased cellular function, decreased regenerative capacity, and changes in the extracellular matrix. External factors such as UV radiation, unhealthy lifestyle choices, and inadequate skin care further aggravate facial skin aging. This screening activity uses the PDCA (Plan-Do-Check-Action) method, which includes planning, implementation, evaluation and corrective action. Facial skin health was assessed using a skin analysis tool, and participants were provided with education regarding preventive measures. This activity consisted of 127 participants (30 men and 97 women). It was found that the average wrinkle, roughness, moist, and UV damage were 26.3%; 24%; 61.4%; and 38.3%. A comprehensive approach including lifestyle modifications, topical treatments, and regular check-ups is essential to reduce the effects of aging and improve skin health in seniors.